Agglomeration and productivity in South Africa: Evidence from firm-level data - Hammed Adedeji Amusa; Njeri Wabiri; David Oluwatosin Fadiran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Using comprehensive, anonymized tax administrative data for the 2008-14 period, we examine firm-level productivity in South Africa. Measures of firm-level productivity are included in a spatial autoregressive model that assesses spillovers from total factor productivity originating from agglomeration economies and the spatial diffusion of productivity shocks. We find that across South Africa's firms, intermediate inputs have the highest impact on firm productivity. The results from the spatial analysis indicate that for a firm in a particular region, its clustering with other firms, having increased market power, and an extended length of stay in a particular region have a greater impact on productivity than do market conditions and firm-specific characteristics associated with firms located in neighbouring regions or municipalities.
Keywords: C23; D24; R11; R12; 330; agglomeration; productivity; South Africa